Dectin-1 signaling coordinates innate and adaptive immunity for potent host defense against viral infection - Kim, Hyeong Won; Ko, Mi-Kyeong; Park, So Hui; Hwang, Seong Yun; Kim, Dong Hyeon; Park, Sun Young; Ko, Young-Joon; Kim, Su-Mi; Park, Jong-Hyeon; Lee, Min Ja (Frontiers in Immunology, 2023)
Background: Most commercial foot-and-mouth disease (FMD) vaccines have various disadvantages, such as low antibody titers, short-lived effects, compromised host defense, and questionable safety. Objectives: To address these shortcomings, we present a novel FMD vaccine containing Dectin-1 agonist, β-D-glucan, as an immunomodulatory adjuvant. The proposed vaccine was developed to effectively coordinate innate and adaptive immunity for potent host defense against viral infection. Methods: We demonstrated β-D-glucan mediated innate and adaptive immune responses in mice and pigs in vitro and in vivo. The expressions of pattern recognition receptors, cytokines, transcription factors, and co-stimulatory molecules were promoted via FMD vaccine containing β-D-glucan. Results: β-D-glucan elicited a robust cellular immune response and early, mid-, and long-term immunity. Moreover, it exhibited potent host defense by modulating host’s innate and adaptive immunity. Conclusions: Our study provides a promising approach to overcoming the limitations of conventional FMD vaccines. Based on the proposed vaccine’s safety and efficacy, it represents a breakthrough among next-generation FMD vaccines.